The impact of short periods of match congestion on injury risk and patterns in an elite football club - Carling, C.; McCall, A.; LeGall, F.; Dupont, G. (British Journal of Sports Medicine, 2016)
Background The effect of fixture congestion on injury rates and patterns has received scarce attention in elite football and existing investigations have not accounted for player rotation or examined the temporal distribution and potential cause of injuries.